2018 15th International Conference on the European Energy Market (EEM) 2018
DOI: 10.1109/eem.2018.8469208
|View full text |Cite
|
Sign up to set email alerts
|

Vertical Transportation Demand Response: Cost of Lost Customer Hours

Abstract: Vertical transportation systems are designed to enhance the people flow. The power consumption of escalators and elevators depends on applied technology, control strategies and passenger flow. Vertical transports are often equipped with energy saving technologies and are eligible for demand response (DR). DR for vertical transports results in induced costs related to increased passenger travel and waiting times. In this article, we analyze the cost of DR by means of speed reduction for elevators and escalators… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…It demonstrated that mean reduced power consumption as the result of DR depends on the passenger arrival rates and, thus, the time of the day. Article [12] introduced the costs of escalator DR in terms of increased passengers queuing and travel times.…”
Section: Previous Researchmentioning
confidence: 99%
See 2 more Smart Citations
“…It demonstrated that mean reduced power consumption as the result of DR depends on the passenger arrival rates and, thus, the time of the day. Article [12] introduced the costs of escalator DR in terms of increased passengers queuing and travel times.…”
Section: Previous Researchmentioning
confidence: 99%
“…Earlier research [11,12] revealed that escalator DR is a viable option for additional power procurement together with the already established methods. However, DR with escalators provided with speed reduction comes at a cost of slowing the passengers.…”
Section: Aims and Problem Statementmentioning
confidence: 99%
See 1 more Smart Citation